The Relationship between the new Leadership Styles and Nursing Productivity - Sahar Mohammed Aly, Maram Taher Alghabbashi, Naemih Marzuqe Alhusyeni, Maryam Mohammed Alkhaybary, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Current and innovative trend leadership styles entail transformational, laissez-faire, passive-avoidant, and transactional leadership styles. Aim: To examine the relationship between nurse leaders’ new leadership styles and nursing productivity at King Fahad Hospital in Al Medina Al Munawara. Material and Methods: A descriptive correlational research design was used to collect the appropriate data. A convenient sampling (n=47) of all nurse's leaders at King Fahad Hospital in Al Madinah Al-Munawara filled three data collection tools. The tools queried demographic data, Multifactor Leadership Questionnaire Rater Form to measure leadership and NHS Knowledge and Skills Framework to measure nurse's productivity. Pearson correlation was used to investigate the correlation further with a significance level of at P= <0.05. Results: Transformational and transactional leadership styles increase staff nurses skills as communication, personnel and Professional development, health safety, security, quality, equality, and diversity. Additionally, the leadership styles improve service improvement, interventions, and treatments. Conclusion and Recommendations: The implementation of transformational and transactional leadership styles is imperative for the nursing practice that seeks to increase the productivity of the nurses, a new leadership style has effect of transactional, transformational, passive-avoidant, and laissez-faire confirms the varied respondents of different demographic groups.